PERIOD ANALYSIS AND MODE IDENTIFICATIONS OF RRab LYRAE STAR X ARIETIS - Bezdenezhnyj, V. P. (Одеські астрономічні публікації, 2007)
On the base of Preston and Paczynski’s (1964) simultaneous photoelectric (U, B, V) and spectroscopic observ ations (358 U-B and 61 Radial Velocities from Lick Single-T rail Spectrograms) has been carried out the analysis of periods of RRab Lyr star X Arietis. It has been given an interpretation of the periods of this star. All these periods were identified as radial overtones of fundamental period and their harmonics. It was proposed rhat this variable star is an multimodal one according to its mode identifications. The comparisons with the periods of AE Bootis, R W Ari, ST CVn, T Sex, BK Dra and V363 Cas are carried out